Comorbidities in the management of patients with lung cancer. Issue 3 (30th March 2017) - Leduc, Charlotte; Antoni, Delphine; Charloux, Anne; Falcoz, Pierre-Emmanuel; Quoix, Elisabeth
Lung cancer represents a major public health issue worldwide. Unfortunately, more than half of them are diagnosed at an advanced stage. Moreover, even if diagnosed early, diagnosis procedures and treatment can be difficult due to the frequent comorbidities observed in these patients. Some of these comorbidities have a common major risk factor, i.e. smoking, whereas others are unrelated to smoking but frequently observed in the general population. These comorbidities must be carefully assessed before any diagnostic and/or therapeutic decisions are made regarding the lung cancer. For example, in a patient with severe emphysema or with diffuse lung fibrosis, transthoracic needle biopsy can be contraindicated, meaning that in some instances a precise diagnosis cannot be obtained; in a patient with chronic obstructive pulmonary disease, surgery may be impossible or should be preceded by intensive rehabilitation; patients with interstitial lung disease are at risk of radiation pneumonitis and should not receive drugs which can worsen the respiratory insufficiency. Patients who belong to what are called "special populations", e.g. elderly or HIV infected, should be treated specifically, especially regarding systemic treatment. Last but not least, psychosocial factors are of great importance and can vary from one country to another according to health insurance coverage. Comorbidities are frequent in patients with lung cancer and impact on their diagnostic and therapeutic management http://ow.ly/7ixJ307cpbL